Novel Strategies to Improve Rituximab Efficacy in Non-Hodgkin's Lymphomas - Massimo Bortolotti; Letizia Polito (Global Journal of Cancer Therapy - Peertechz Publications, 2015)
Non-Hodgkin's lymphomas (NHLs) are the second fastest growing cancer in terms of incidence and deaths in the United States and Europe. NHLs are a heterogeneous cancer group including several haematological neoplasias with different degree of aggressiveness. In spite of the progresses, conventional therapies do not ensure long-term survival [1]. The NHL patients, who have a poor life expectation, could take advantage from innovative therapeutic strategies, such as immunotherapy. Specific antibodies can preferentially bind tumour cells over normal tissues. This specificity is based upon characteristics (surface antigens) that are completely independent from the parameters that allow for differential toxicity of chemo- and radiotherapy. The vascular nature of most lymphomas and their antigen expression make these tumours a favourable setting for treatment with monoclonal antibodies. In fact, the first successful use of antibodies as treatments for cancer was demonstrated in NHLs [2,3]. CD20 has been largely exploited as target antigen for immunotherapy with antibodies because it is expressed at high levels on B-lymphoma cells and is not expressed on stem cells [4].